ANALISIS KONTEN VIDEO IKLAN PADA APLIKASI TIKTOK UNTUK MENINGKATKAN BRAND AWARENESS - I Putu Dharmawan Suryagita Susila Putra (Nusantara Hasana Journal, 2022)
The use of social media is very influential for various groups including the business world. One of the benefits is being able to support access to marketing communications during the product promotion process, and building brand awareness. One of the most widely used social media applications today is the TikTok application. TikTok is listed on the Playstore as an application that has 500 million downloads. This research is intended to explore, study, analyze and understand the potential of the TikTok application in increasing brand awareness. The purpose of this study was to analyze the ad video content on the tiktok application in increasing brand awareness. The research method used in this study is a qualitative descriptive research method. The data collection technique that will be used in this study uses data collection techniques on various books, literature, and various reports related to research variables, this study uses data collected by observation techniques in the TikTok application on the @goodponsel account. This research shows that @goodponsel in each uploaded video content gets an average of up to thousands of viewers for each video. if you look closely, the video content created by @goodponsel contains elements of non-rational persuasive advertisements. Using non-rational persuasion, invites viewers to continue to listen to the video advertisements made by @goodponsel, and of course this will build brand awareness of GoodPhone.